2013
DOI: 10.1177/1473325013496597
|View full text |Cite
|
Sign up to set email alerts
|

How images work: An analysis of a visual intervention used to facilitate a difficult conversation and promote understanding

Abstract: This study centers on an intervention that uses visual methods to structure conversations among teachers about their undocumented Latino/Latina immigrant students living in the US. Given negative perceptions of undocumented immigrants and cultural misunderstandings, recent demographic shifts have challenged many communities, and presented issues especially relevant to majority-culture teachers who teach immigrant students. We describe an innovative intervention methodology that incorporates photographs with fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The images, captions, and discussions seemed to raise teachers' awareness about the life experiences of Latino/Latina immigrant families and elicited empathic emotional connections. Findings also indicated shifts in attitudes among some teachers and motivation to interact with Latino/Latina students and parents in more sensitive and understanding ways (Chapman et al, 2014a). Taken together, findings from our qualitative study and these two pilot studies indicate that the visual approach to professional training aimed at facilitating reflection and conversation used in Yo Veo was effective in influencing educators' attitudes, knowledge, and behavior regarding Latino/Latina immigrants; however, the effects may be moderated by the school context.…”
Section: Discussion and Applications To Social Workmentioning
confidence: 52%
See 2 more Smart Citations
“…The images, captions, and discussions seemed to raise teachers' awareness about the life experiences of Latino/Latina immigrant families and elicited empathic emotional connections. Findings also indicated shifts in attitudes among some teachers and motivation to interact with Latino/Latina students and parents in more sensitive and understanding ways (Chapman et al, 2014a). Taken together, findings from our qualitative study and these two pilot studies indicate that the visual approach to professional training aimed at facilitating reflection and conversation used in Yo Veo was effective in influencing educators' attitudes, knowledge, and behavior regarding Latino/Latina immigrants; however, the effects may be moderated by the school context.…”
Section: Discussion and Applications To Social Workmentioning
confidence: 52%
“…At School 1, qualitative data were collected and analyzed, which has been published elsewhere (Chapman et al, 2014a). These findings indicated that the images initially engaged the teachers in the story of the immigrant child and her family as depicted in the photography series.…”
Section: Discussion and Applications To Social Workmentioning
confidence: 95%
See 1 more Smart Citation
“…A qualitative study from the social work field, conducted at the University of North Carolina, Chapel Hill, examined an intervention in which VTS was used in diversity training for teachers (Chapman et al 2013). The researchers looked at both "schema change" and how images function in catalyzing dialogue.…”
Section: Impact Shown In Healthcare Educationmentioning
confidence: 99%
“…For example, of the seven full articles published in Issue 4 (2014), two papers used visual methods in their studies. Chapman et al (2014) used photographs to examine the ways in which images function to facilitate difficult discussions and can be used to stimulate shifts in attitudes. In the second paper, Moshoula Capous Desyllas (2014) describes the use of photovoice with sex workers.…”
mentioning
confidence: 99%